Lingkungan Budaya, Politik Dan Hukum Global - Suhairi, Suhairi; Suri, Dian Mei; Nasution, Khairunnisak; Ritonga, Nurul Amelia Pratiwi; Anandani, Thalia (Lembaga Riset, Publikasi dan Konsultasi JONHARIONO, 2023)
This article discusses everything related to the global cultural, political and legal environment. In running the economy, every country has rules that must be understood by everyone who carries out trading activities. This article aims to provide readers with understanding and insight regarding the quite complex dynamics of the cultural, political and legal environment at the global level. In understanding political and legal policies at the global level, this article provides an understanding related to global level policies